Rúbrica de evaluación docente para mejorar el registro de las calificaciones de los estudiantes de la U.E. Federico Froebel, babahoyo.2022 - MACIAS GARCIA, CRISTINA ALEXANDRA (2024)
The purpose of the present investigation is to demonstrate the impact of the evaluation rubrics on the learning results of 92 Higher Basic Education students of the “Federico Froebel” 2022 Educational Unit using bibliographic and field research methods, for this, surveys of teachers and students, which allowed us to collect information with a view to understanding the circumstances that affect the evaluation system of the Froebelian institution, the students' fear of evaluation and the teacher's lack of knowledge affect the development of skills and abilities of the students. Thus, the evaluation rubrics become a favorable tool to improve the learning evaluation process implemented by teachers with a view to feeding back the learning-teaching process.